1286 Closing the gaps between occupational and environmental exposures and human health. (24th April 2018) - Adam, Balazs; Scheepers, Paul TJ; Schlünssen, Vivi; Damme, Karel Van; Bolognesi, Claudia; Sigsgaard, Torben; Göen, Thomas; O'Kennedy, Richard; Casteleyn, Ludwine; Budnik, Lygia Therese
Abstract : Introduction: The World Health Organisation has ranked environmental exposures among the top risk factors for chronic disease mortality. Worldwide 55 million people die each year from non-communicable diseases (NCD) including cancer, diabetes, chronic cardiovascular, respiratory, and neurological diseases. Methods: The EU-funded project Diagnosis, Monitoring and Prevention of Exposure Related Non-Communicable Diseases (DiMoPEx) aims at developing new concepts for a better understanding of health-environment (including gene-environment) interactions in the aetiology of NCDs. The project is advancing within several working groups, which cover the areas of exposure assessment, toxicology, epidemiology, ethical issues, biomarkers of genetic effects and epigenetic and clinical characteristics of NCDs. Results: DiMoPEx partners have identified some of the emerging research needs, including evidence-based exposure data, animal models reflecting total human life-span and low dose cumulative exposures. From the perspective of epidemiology the gaps between risk factor and health outcome may be bridged by biomarker-based research in which well-designed experimental exposure studies and biomarkers of early response should play a central role. DiMoPEx identified several drawbacks in existing studies on exposure-NCD association, e.g. inappropriate study design or suboptimal patient recruitment and sample collection as well as poor data interpretation. As a consequence such studies sometimes do not provide results of desired quality. In occupational and environmental health the use of biomarkers is embedded in a process called human biological monitoring with its standard performance rules. Studies addressing health outcomes in relation to exposures in the living and working environment often do not sufficiently account for existing knowledge regarding proper exposure measures in their study design (e.g. recording only ever/never exposed or self-reporting of chemicals which can lead to exposure misclassification). Discussion: DiMoPEx will focus on closing the gap between exposure and disease by extracting and organising evidence-base exposure data, which may support the diagnosis and prevention of NCDs.